Respuesta :

bcalle
f(x) = x^2 + 4x - 5

[f(a + h) - f(a)] / h

f(a) = a^2 + 4a - 5
f(a + h) = (a + h)^2 +4(a + h) - 5
             = a^2 + 2ah + h^2 + 4a + 4h - 5

f(a + h) - f(a) = a^2 + 2ah + h^2 + 4a + 4h - 5 - ( a^2 + 4a - 5)
----------------      ------------------------------------------------------------
       h                                              h

                       =  2ah + h^2 + 4h            h (2a + h + 4)          2a + h + 4
                           -------------------        =  -------------------    =
                                       h                              h